Opaque Distribution Channels for Competing Service Providers: Posted Price vs. Name-Your-Own-Price Mechanisms - Chen, Rachel R.; Gal-Or, Esther; Roma, Paolo (Operations Research, 2014)
Opaque selling has been widely adopted by service providers in the travel industry to sell off leftover capacity under stochastic demand. We consider a two-stage model to study the impact of different selling mechanisms, posted price (PP) versus name-your-own-price (NYOP), of an opaque reseller on competing service providers who face forward-looking customers. We find that in this environment, providers prefer that the opaque reseller uses a posted price instead of a bidding model. This is because the ability to set retail prices is critical for extracting surplus from customers who wait to purchase from the reseller. Such surplus extraction enables providers to set high prices for advance sales and obtain high profits. The dominance of PP over NYOP disappears, however, when competition between sellers is minimal or absent. We extend our model to multiple opaque resellers who compete in selling off last-minute capacity for service providers and find that our main insights continue to hold with differentiated resellers. Despite providers' preference in favor of PP, there are circumstances under which the opaque reseller earns higher profits under NYOP. Leisure customers might also prefer the bidding mechanism, which allows them to retain some surplus. This can help explain the rapid growth of the NYOP model over the last decade. Our findings are consistent with the evolution of opaque selling in the travel industry, and in particular, the recent trend towards more published price sales for opaque products.